Environmental fertility research at the turn of the century - Bonde, Jens Peter (Scandinavian Journal of Work, Environment & Health, 1999)
Research into environmental causes of impaired human fertility is still immature. Knowledge on the strengths and limitations of several research options, the main sources of bias, the occurrence of infertility and subfecundity in several countries, the patterns of contraceptive behavior, and the distribution of sperm counts at the population level has advanced, but the much-debated questions about temporal and regional trends in fertility and semen quality remain unsettled. Refined biological markers of male fecundity and markers feasible for large-scale studies of female fecundity are needed. The effects of several life-style factors have been characterized successfully, but the detrimental effects of environmental exposures have not. Most studies are either inconclusive or fail to demonstrate any important risks. If comprehensive knowledge on biological mechanisms is a criterion of maturity, epidemiologic and toxicologic fertility research is young. The new millennium will be challenged to determine the role played by the environment in developed countries, wrong exposure time windows, too crude or inappropriate measures of fertility, and overlooked critical exposures.
Keywords: environment; fecundity; fertility; human; life-style; occupation; research method; secular trend; toxicity